Synthesis, computational molecular docking analysis and effectiveness on tyrosinase inhibition of kojic acid derivatives - TÜRE, ASLI (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2019)
Tyrosinase inhibitors have become increasingly important as whitening agents and for the treatment of pigmentary disorders. In this study, the synthesis of kojic acid derivatives having 2-substituted-3-hydroxy-6-hyroxymethyl/chloromethyl/methyl/morpholinomethylpiperidinyl- methyl/pyrrolidinylmethyl-4H-pyran-4-one structure (compounds 1-30) with inhibitory effects on tyrosinase enzyme were described. One-pot Mannich reaction was carried out by using kojic acid/chlorokojic acid/allomaltol and substituted benzylpiperazine derivatives in presence of formaline. Subsequently, cyclic amine (morpholine, piperidine and pyrrolidine) derivatives of the 6th-position of chlorokojic acid were obtained with nucleophilic substitutions in basic medium. The structures of new compounds were identified by FT-IR, H-1- and C-13 NMR, ESI-MS and elemental analysis data. The potential mushroom tyrosinase inhibitory activity of the compounds were evaluated by the spectrophotometric method using L-DOPA as a substrate and kojic acid as the control agent. The potential inhibitory activity was also investigated in silico using molecular docking simulation method. Tyrosinase inhibitory action was significantly more efficacious for several compounds (IC50: 86.2-362.1 mu M) than kojic acid (IC50: 418.2). Compound 3 bearing 3,4-dichlorobenzyl piperazine moiety was proven to have the highest inhibitory activity. The results of docking studies showed that according to the predicted conformation of compound 3 in the enzyme binding site, hydroxymethyl group provides a metal complex with copper ions and enzyme. Thus, this interaction explain the high inhibitory activities of the compounds 1, 3 and 4 possessing hydroxymethyl substituent supporting the mushroom assay results with docking studies. In accordance with the results, it is suggested that Mannich bases of kojic acid bearing substituted benzyl piperazine groups (compounds 1, 3, 4, 11, 13, 14, 23, 24, 28, and 29) could be promising antityrosinase agents. Additionally, considering the relationship between tyrosinase inhibitory activity results and molecular docking, a new tyrosinase inhibition mechanism can be proposed.
Keywords: Kojic acid; Mannich reaction; Tyrosinase inhibition; Molecular docking; MUSHROOM TYROSINASE; DESIGN; ANALOGS; VITRO